Minke whales maximise energy storage on their feeding grounds - Christiansen, Fredrik; Víkingsson, Gísli A.; Rasmussen, Marianne H.; Lusseau, David (Journal of Experimental Biology, 2013)
Seasonal trends in energy storage of the minke whale ( Balaenoptera acutorostrata ), a capital breeder, were investigated in Iceland, a North Atlantic feeding ground. The aim was to better understand the energy acquisition strategies of minke whales and the energetic costs that different reproductive classes face during the breeding season. We modelled total blubber volume, using blubber thickness and morphometric measurements of individual whales. Blubber volume was influenced by body length, and was higher for pregnant females than mature whales. Blubber volume increased linearly through the feeding season at the same rate for mature (mean ± s.e.m.=0.0028±0.00103 m3 day−1; N =61 male, 5 female) and pregnant whales (0.0024±0.00100 m3 day−1; N =49), suggesting that minke whales aim to maximise energy storage while on the feeding grounds. The total amount of blubber accumulated over the feeding season (0.51±0.119 m3 for mature and 0.43±0.112 m3 for pregnant whales), together with energy stored as muscle and intra-abdominal fats, constitutes the total amount of energy available for reproduction (fetus development and lactation) on the breeding grounds, as well as migration, daily field metabolic rates, growth and body maintenance. No seasonal variation was observed for immature whales ( N =4 male, 12 female), suggesting that they are investing most of their excess energy into growth rather than reproduction, in order to reach the length of sexual maturity faster and start reproducing earlier. Our novel modelling approach provides insight into large whale bioenergetics and life history strategies, as well as the relationship between single-site measurement of blubber thickness and total blubber volume.